Digital Payment Interoperability and Financial Inclusion in The Gambia: Policy Priorities for a Resilient Central Banking Framework - Ratri Buda Nugrahanti; Tantri Widiastuti (Jurnal Ilmiah Aset, 2026)
The expansion of mobile money, digital payments, and platform-based financial services is reshaping the role of central banks in promoting financial inclusion, payment efficiency, and system stability. In The Gambia, digital financial services offer important opportunities to widen access to finance and improve the performance of the national payments ecosystem. However, these gains may remain limited where providers operate in fragmented ways and interoperability remains weak. This paper examines how digital payment interoperability can strengthen financial inclusion and support a more resilient central banking framework in The Gambia. Drawing on a qualitative policy-analysis approach based on literature review, regulatory analysis, and contextual assessment of The Gambia within the broader African and ECOWAS digital finance landscape, the paper identifies the principal institutional, market, and governance barriers that constrain interoperable digital payments. The analysis shows that fragmented payment rails, uneven regulatory coordination, weak integration across providers, and infrastructural and literacy constraints can reduce user convenience, increase transaction costs, and weaken payment-system resilience. The paper argues that interoperability should be treated not merely as a technical issue, but as a strategic policy instrument through which the Central Bank of The Gambia can advance inclusion, efficiency, trust, and financial-system resilience. It concludes by proposing policy priorities around common standards, proportionate regulation, infrastructure investment, consumer protection, cybersecurity, and phased regional alignment within ECOWAS